L'Art en Campagne 96 : Art contemporain 1960-1990 - Moxhet, Albert; Roggeman, Willem M.; Verbrugghen, Jo (Liège : Fondation 7 A, 1996)
Adami, Valerio ; Alechinsky, Pierre ; Andrien, Mady ; Antoine, Paul ; Arman ; Bage, Jacques ; Belgeonne, Gabriel ; Blake, Peter ; Boetti, Alighiero ; Broodthaers, Marcel ; Buren, Daniel ; Burssens, Jan ; Bury, Pol ; César ; Chadwick, Lynn ; De Almeida, Charters ; Chia, Sandro ; Christo ; Claerhout, Jef ; Claus, Hugo ; Cleeremans, Ralph ; Combas, Robert ; Courtois, Pierre ; Crombé, Patrick-Frederick ; Cucchi, Enzo ; D'Haese, Roel ; De Maeyer, Jacky ; de Saint Phalle, Niki ; de Villiers, Jephan ; Decelle, Philippe ; Dierickx, Karel ; Dodeigne, Eugène ; Dries, Jan ; Dudant, Roger ; Errò ; Flanagan, Barry ; Frankinet, Laure ; Frantzen, Tom ; Gailliard, Jean-Jacques ; Hamilton, Richard ; Hoenraet, Luc ; Jacobsen, Robert ; Kirkeby, Per ; Kounellis, Jannis ; Leroy, Christian ; Lismonde ; Lüpertz, Markus ; Mandelbaum, Arié ; Mariën, Marcel ; Mazy, Marcel ; Mendelson, Marc ; Monory, Jacques ; Monteyne, Roland ; Neumann, Max ; Paladino, Mimmo ; Panamarenko ; Pasque, Aubin ; Plomteux, Léopold ; Ransonnet, Jean-Pierre ; Raveel, Roger ; Raysse, Martial ; Reinhoud ; Rener, René-Maria ; Rhaye, Yves ; Roulin, Félix ; Somville, Roger ; Spilliaert, Pol ; Strebell, Vincent ; Tapta ; Tinguely, Jean ; Trampedach, Kurt ; Tsoclis, Costas ; Choffray, Francine Urbin ; Van Breedam, Camiel ; Van Gysegem, Paul ; Van Severen, Dan ; Van Sumere, Hilde ; vandeberg, Diana ; Vandercam, Serge ; Venet, Bernar ; Verduyn, Jacques ; Wercollier, Lucien ; Wittevrongel, Roger ; Wyckaert, Maurice
biografie
L'Art en Campagne 96 : Art contemporain 1960-1990, Fourneau St.-Michel et Basilique, Saint-Hubert, 14-22 september 1996
Frans & Nederlands
boek